Force Push: Exploring Expressive Gesture-to-Force Mappings for Remote Object Manipulation in Virtual Reality - Yu, Run; Bowman, Doug A. (Frontiers in ICT, 2018)
This paper presents Force Push, a novel gesture-based interaction technique for remote object manipulation in virtual reality (VR). Inspired by the design of magic powers in popular culture, Force Push uses intuitive hand gestures to drive physics-based movement of the object. Using a novel algorithm that dynamically maps rich features of hand gestures to the properties of the physics simulation, both coarse-grained ballistic movements and fine-grained refinement movements can be achieved seamlessly and naturally. An initial user study of a limited translation task showed that, although its gesture-to-force mapping is inherently harder to control than traditional position-to-position mappings, Force Push is usable even for extremely difficult tasks. Direct position-to-position control outperformed Force Push when the initial distance between the object and the target was close relative to the required accuracy; however, the gesture-based method began to show promising results when they were far away from each other. As for subjective user experience, Force Push was perceived as more natural and fun to use, even though its controllability and accuracy were thought to be inferior to direct control. This paper expands the design space of object manipulation beyond mimicking reality, and provides hints on using magical gestures and physics-based techniques for higher usability and hedonic qualities in user experience.